Avaliação da influência da terapia por infliximabe na cicatrização óssea de alvéolos dentários pós-exodontia em ratos - Ferreira Júnior, Antonio Ernando Carlos (2016)
Bone healing after tooth extraction depends on variables such as surgical technique, local and systemic factors and use of pharmacological substances. Anti-inflammatory drugs can alter the tissue repair, interfering with the inflammatory phase of healing. Infliximab is a chimeric monoclonal antibody, human-murine anti-Tumor Necrosis Factor alpha (TNF-α) which has been widely used to replace corticosteroids in rheumatology clinic because it has fewer side effects in the long term. However, TNF-α pathway acts directly on osteoclastogenesis, can change the physiological response of bone turnover and its inhibition may lead to immunosuppression, increasing the risk of local infection. It was aim of this study to evaluate the influence of infliximab in healing after dental extractions alveoli. For this purpose, 84 Wistar rats (n = 7) were randomized into two groups (infliximab EV 5 mg / kg or saline EV 1ml / kg, pre-treated with 4 weekly administrations prior to extraction, weekly maintained until the day of sacrifice) . The animals were sacrificed 1, 3, 7, 14, 21 and 28 days after surgery. The occurrence of root fractures, surgical time and the weight of extracted teeth were recorded. On the day of sacrifice the weight of animals and organs (liver, spleen, kidneys, stomach) were measured. After fixation in 10% formalin buffered and macroscopic analysis, jaw and fragments of these organs, followed for histological processing and microscopic study. The jaws were submitted to radiographic, histomorphometric (size of the deposition of scar tissue, percentage of area represented by bone tissue and number of polymorphonuclear neutrophils, mononuclear and osteoclasts), immunohistochemistry (Picrossirius Red) and immunohistochemistry (TNF-α) . There were no differences seen in determining the radiolucent area related to post-extraction site between the experimental groups (p = 0.646). However, the histomorphometric analysis was visualized lower completion by bone and a greater amount of tissue remaining in infllximabe group significantly on day 14 (p <0.001). Furthermore, a smaller number of polymorphonuclear neutrophils in 3 (p <0.01) and 7 days (p <0,001) mononuclear on the 7th day (p <0.01) and osteoclasts in the 7th and 14th days (p < 0.01 and p <0.001, respectively) were observed. It also observed lower TNF-α immunoreactivity in the post-extraction sites on days 7,14, 21 and 28 (p <0.01; p <0.05, p <0.05 and p <0.01 respectively). We conclude that TNF-α inhibitors may alter the bone repair capacity in post-extraction sites. These findings suggest the need for further precautions in gory dental procedures in patients undergoing systemic therapy of these drugs.